Strategi Promosi melalui Media Sosial dalam Meningkatkan Jumlah Siswa di SMP Fajrul Islam dalam Perspektif Islam - Sukarna, Sukarna (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
This study aims to determine promotion strategies through social media in increasing the number of students at SMP Fajrul Islam, research methods. namely a descriptive qualitative method that emphasizes observing a phenomenon and researching more on the substance of the meaning of the phenomenon. The results of the study stated that in carrying out a promotion strategy to get students it could be done in two ways, namely 80% utilization of social media such as WhatsApp, Facebook. And Instagram. The 20% is done by going directly to the field promotions. The proper use of social media to promote schools is able to prove that schools can compete healthily to gain a good image in the eyes of society. The use of promotional social media can be done effectively and efficiently because it doesn't take up a lot of time so it can be done anytime and anywhere. continue to instill the most important religious teachings such as having a dhuha prayer program every morning, reading and writing the Koran, tahfidz qur'an, safinah books and muhadhoroh as a way to continue to instill Islamic Sharia in schools.